Protection against periodontal destruction in diabetic condition with Sardinella longiceps fish oil: expression of matrix-metalloproteinase 8 and tissue inhibitor of metalloproteinase 1 - Dian Widya Damaiyanti; Dian Mulawarmanti; Kristanti Parisihni (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: There is strong evidence to support the claim that periodontitis may be more prevalent among diabetic individuals. Collagen degradation represents one of the key events in periodontal destructive lesions. The level of matrix metalloproteinase 8 (MMP-8) and tissue inhibitor of metalloproteinase 1 (TIMP-1) are key to periodontal collagenolysis and associated with the severity of periodontal inflammation and disease. Host modulatory therapy has been proposed as a treatment for periodontal diseases. Sardinella longiceps (lemuru) fish oil containing polyunsaturated fatty acids (PUFAs), including omega 3 and 6, has been shown to possess therapeutic anti-inflammatory and protective properties effective against inflammatory diseases, including periodontitis. Purpose: The study aimed to examine the effect of dietary supplementation of Sardinella longiceps fish oil on protection against periodontal destruction resulting from the expression of MMP-8 and TIMP-1. Methods: Wistar rat samples are divided into four groups: a negative control group and three groups receiving Sardinella longiceps fish oil treatment (4 ml/ weight (Kg), 8 ml/ weight (Kg) and 16 ml/ weight (Kg). One week before treatment, all groups were administered with streptozotocin (STZ) 65 ml/ weight (Kg) and nicotinamide 110 ml/ weight (Kg) to induce diabetic conditions. Immunohistochemistry slides of periodontal tissues were prepared after three weeks of treatment. The expression of MMP-8 and TIMP-1 was counted using the HSCORE index, data was analyzed by means of non-parametric methods using Kruskal-Wallis, and Mann-Whitney tests. Results: Statistical analyses confirmed a significant increase in MMP-8 expression and a reduction in TIMP-1 expression in the negative control group compared to the treatment group (p<0.05). Meanwhile, the treatment group showed a significant reduction in MMP-8 expression and a marked increase in TIMP-1 expression, with the best result produced by the administering of 16 ml/ weight (Kg) Sardinella longiceps fish oil to the treatment group (p<0.05). Conclusion: Dietary supplementation of Sardinella longiceps fish oil can protect against periodontal destruction under diabetic conditions, by decreasing MMP-8 expression and increasing TIMP-1 expression.